HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN KONTROL GULA DARAH DAN OLAHRAGA PADA PENDERITA DIABETES MELITUS - Siti Aisyah; Yesi Hasneli; Febriana Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Diabetes Mellitus is heterogen abnormalities that characterized by hyperglycemia. The management of diabetes mellitus were blood glucose control and physical exercise. The purpose of this research was to know the correlation between family support with blood sugar control and physical exercise in diabetes mellitus patient. The designed of this research was quantitative research with cross sectional approach. The sample were 83 respondents that chased by inclusion criteria used purposive sampling technique. Instrument used questionnaires. The analysis was univariate to know the frequency of distribution and bivariate used chi square test α (0,05). The result showed there was correlation between family support and blood glucose control (p value 0,034), and there was correlation between family support and physical exercise in diabetes mellitus patients (p value 0,000). Based on the results of the study it’s expected for health services can provided information and identify family support issues, blood glucose control and physical exercise with efforts to improved health care in diabetic patients. Therefore, it can improved optimal treatment. Keywords: blood glucose control, diabetes mellitus, family support, physical exercise